The Influence of the Use of Role Playing Methods and Interest in Learning on the English Speaking Ability - Sunandar, Sunandar; Alvarez, Ana Sofia Izquierdo; Cardozo, Cristian Andres (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This study aims to evaluate the effect of using role-playing methods and interest in learning on the English speaking abilities of class IX students at Junior high school 2 Merangin. The research design follows a 2x2 factorial design with pretest and posttest, where one factor is the use of role-playing methods and the other factor is interest in learning. The subjects of this research were class IX students at Junior high school 2 Merangin. The instruments used include questionnaires to measure students' interest in learning and oral tests to measure students' English speaking abilities. The data analysis techniques used include descriptive analysis for questionnaires, parametric statistical tests such as the t-test and analysis of variance (ANOVA) test for oral test data, as well as correlation analysis to determine the relationship between students' interest in learning and speaking ability. It is hoped that the results of this research can provide a deeper understanding of the effectiveness of the role-playing method in improving students' English speaking skills, as well as understanding how interest in learning influences the language learning process. It is hoped that the implications of this research can make a positive contribution to the development of more effective learning strategies in the field of language at the secondary school level.